The history of Australia - Clarke, F. G. (Francis Gordon), 1943- (Greenwood histories of the modern nations., 2002)
Australian history has been written for over two centuries beginning with European explorers and colonists attempting to convey something of the complexity of the strange upside-down world they encountered in the southern hemisphere. Of course, aboriginal peoples had lived in Australia for millennia before the arrival of the whites. Modern Australia has its foundations in these two cultural strands. Intertwined with these are the impact of colonialism and federation, indentured servitude and convict transportation, the effects of El Nino on European-style farming techniques, gold rushes, and longstanding issues of ethnicity, immigration, and religious tolerance. Covering these topics and more, this most recent and up-to-date narrative history of Australia includes a timeline of major events, a biographic sketches of noteworthy historical figures, and a bibliographic essay.